Mammographic evaluation of palpable breast masses with pathological correlation: a tertiary care centre study in Nepal - Gurung, G; Ghimire, RK; Lohani, B (Journal of Institute of Medicine Nepal, 2011)
Introduction: Breast cancer is one of the major health problem for all countries. . In Nepal , breast cancer is the second most common cancer in female. Early detecting tools like mammography can able to detect location , size, morphology, and nature of breast lesions that can help to reduced mortality and morbidity from breast cancer significantly. Methods: This prospective study was carried out at the department of Radiology, Surgery and Pathology for a period of one year. A total of 100 patients with clinically palpable breast lump were subjected to mammography and subsequently to FNA or biopsy. The mammograms were reviewed by two senior consultant radiologists and pathology by a senior pathologist. Results: Out of 100 patients, 65% had mammographic features of benign lesion and 35% had features of malignancy. Pathology revealed 64% of lesion to be benign and 36% of lesion to be malignant. There were four false negative (6.2%) and three false positive (8.6%) cases. The sensitivity and specificity of mammography were 88.9% and 95.53% respectively. The mean age of patient with malignant lesion was 46.3 years (SD=11.5) and 34.7 years (SD=10.6) for benign lesions. Among malignant lesion 37.1% had lobulated, 14.3% had oval, 31.4% round and 17.1% had irregular shape with spiculated margin in 60% and indistinct margins in 34.3%. Among benign 7.7% showed lobulated shape, 41.5% oval and 50.8% round shape. Circumscribed margin was found in 93.9% of benign and 5.7% of malignant lesions. Punctuate and polymorphic calcification was found in malignant lesions (25.7% and 5.7%). Secondary changes were found in only in the malignant cases. Halo sign was found only in benign cases and most common in fibroadenoma (38.4%). Conclusions: Mammography is an effective diagnostic tool for benign and malignant characteristic of palpable breast mass. Keywords: Breast lump; mammography; micro calcification DOI: http://dx.doi.org/10.3126/joim.v32i2.4940 Journal of Institute of Medicine, August, 2010; 32: 21-25